Cross-calibration of pencil-beam (DPX-NT) and fan-beam (QDR-4500C) dual-energy X-ray absorptiometry for sarcopenia - Ito, Kenyu (Nagoya J Med Sci, 2015)
Sarcopenia, defined as the loss of muscle mass accompanied by weakness, is an important factor leading to frailty and is a growing concern in the aging Japanese society. Muscle mass can be calculated by dual-energy X-ray absorptiometry (DXA), but results differ between devices produced by different manufactures. Thus, cross-calibration is needed to compare body composition results in multicenter trials or when scanners are replaced. The purpose of this study was to perform an in vivo calibration of total body scans between pencil-beam (DPX-NT, GE Healthcare) and fan-beam (QDR-4500C, Hologic Inc.) DXA units. A total 30 subjects (15 women, 15 men, mean age = 35 years, range 22–49 years) were recruited. The lumbar bone mineral density (BMD), femoral neck BMD, appendicular fat and lean body mass, and the appendicular skeletal muscle mass index (ASMI) were highly correlated (r = 0.979–0.993, r(2) = 0.889–0.977). The conversion formulas were as follows: lumbar BMD, Y = –0.08 + 1.16X (X = QDR-4500C, Y = DPX-NT), femoral neck BMD, Y = –0.015 + 1.11X, and ASMI Y = 0.92 + 0.90X. There is excellent comparability between the DPX-NT and the QDR-4500C DXA units. However, cross-calibration equations are required to assess muscle volume, fat, and ASMI in multicenter studies investigating sarcopenia.